HERZBERG’S MOTIVATION-HYGIENE AND JOB SATISFACTION IN THE MALAYSIAN RETAIL SECTOR: MEDIATING EFFECT OF LOVE OF MONEY - Tan Teck-Hong; Amna Waheed (Asian Academy of Management Journal, 2011)
This paper examines what motivates employees in the retail industry, and their level of job satisfaction using Herzberg’s hygiene factors and motivators. In this study, sales personnel were selected from ladies clothes stores in the shopping mall of Bandar Sunway, Selangor using convenient sampling. The results have showed that hygiene factors dominated motivators in terms of job satisfaction of sales personnel in Malaysia. The working condition was the most significant factor in motivating sales personnel. Recognition was second, followed by company policy, and money factor. There is a need to dwell deeper into the reasons behind why salespeople placed such high importance on money. Further analysis was performed to assess to what extent the love for money mediates the relationship between salary and job satisfaction. Based on the general test for mediation, the love of money could explain why there is a relation between salary and job satisfaction. The main implication of this study is that sales personnel who value money highly are satisfied with their salary and job when they receive a desired raise.